Identifying the Phenomenon of monopoly according to the vision of Accounting - سلمان, عامر محمد; احمد, رزكار علي (Journal of Economics and Administrative Sciences, 2015)
The research seeks to identify the factors affecting the monopoly and the possibility of measuring the phenomenon of economic ( monopolistic profit) accounted for and that the importance of research topic arising from the transformation of the majority of developing countries to the market economy, which represents the image of the capitalist economy, which is a monopoly, a stages that economy in its various forms, whether Market Worldwide sales monopoly or monopoly, which generates absolute monopolistic profits, which more or less affect on the overall economy of those countries than they should study the phenomenon of monopoly and its impact on the economies of those countries that still love to find her site reinforces its position in the market economy. As manifested that the process of measuring  monopolistic profit fall within the measurement method derived by measuring the intangible assets, which are the factors that lead to the phenomenon of monopoly and there are intangible assets critical to add value for the unit and economic factors are affecting the monopoly, namely: human capital, capital structural , relational capital, customers, acquisition of technology, so this added value be profitable within a monopolistic profit shown in the income statement As long as the science of accounting is one of the open science should with other social sciences and added to study the environmental, social and economic phenomenon, including the monopoly, should face the challenges of accounting measurement resorting to innovative ways of measuring the derivative and arbitrary measure of monopoly profit